Stress promotes reproduction in the annual fish Austrolebias reicherti. (April 2021) - Passos, Carlos; Reyes, Federico; Jalabert, Cecilia; Quintana, Laura; Tassino, Bettina; Silva, Ana
Abstract : Glucocorticoids (GCs) regulate metabolism and energy balance by mediating physiological and behavioural responses to stress. Vertebrates respond to environmental challenges by increasing GC levels, which mediate the reallocation of resources from delayable activities such as reproduction to immediate survival necessities. However, when future reproductive potential is low, it has been hypothesized (and evidenced in a few semelparous species) that stress should adaptively promote reproduction rather than suppress it, even at the expense of wellbeing. Due to their unique life cycle and particular habitat, annual fishes (Cyprinodontiformes, Aplocheiloidei) are ideal unexplored model systems to test the prediction that GCs promote reproduction. Annual fishes are among the most remarkable extremophile species with the shortest vertebrate life span. They inhabit ephemeral ponds, and after reaching sexual maturity in few weeks, they breed continuously. As the breeding season progresses, and pond dry-out is imminent, future mating opportunities decrease together with the impoverishment of environmental conditions. In this study, we evaluate, for the first time in annual fishes, how reproduction is affected by high GC levels. We first show that male Austrolebias reicherti increase their cortisol levels as the breeding season progresses and environmental conditions deteriorate in the wild. Furthermore, increased cortisol levels in males were associated with increases in female gonadosomatic (GSI) and hepatosomatic (HSI) indices and a decrease in male HSI. Secondly, we show that cortisol treatment induces (1) an increase in male courtship behaviour and in the intensity of male typical coloration, (2) a weight loss in males and (3) an increase in female HSI. Overall, we demonstrate that cortisol promotes reproduction in both sexes of A. reicherti with sexually distinct effects, representing a clear exception to the traditional role of the stress response impairing reproduction. Highlights: The canonical effect of stress on reproduction is reverted in annual fish. As mating opportunities run out, cortisol levels and reproductive effort increase. Cortisol treatment promotes courtship and bold coloration in males. Annual fish arise as ideal models to test the link between stress and life history.